MACROSCOPIC LESION HEALING IN DOGS WITH ATOPIC DERMATITIS FOLLOWING COCONUT OIL ADMINISTRATION - Adi Setiawan; Putu Devi Jayanti; Ni Nyoman Werdi Susari; Luh Made Sudimartini; I Nyoman Suartha (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Atopic dermatitis is a multifactorial disease associated with inflammatory and pruritic allergic conditions, with a genetic predisposition and immunoglobulin E (IgE) production against environmental allergens. To address this disease, the use of coconut oil as a herbal medicine may serve as an alternative therapy. This study aimed to evaluate changes in macroscopic skin lesions in dogs with atopic dermatitis following coconut oil administration. The study used five Balinese local breed dogs with atopic dermatitis aged three months. The dogs received coconut oil massage treatment once every three days for 33 days. The research procedure involved observing the progression of primary and secondary lesion healing, hair growth around the lesion area, and microscopic examination of the hair growth phase. The data were analyzed using nonparametric tests, followed by the Friedman test, Wilcoxon test, and regression analysis. The results of the Friedman, Wilcoxon, and regression tests showed significant healing after coconut oil application, with statistically significant differences (P < 0.05) in macroscopic observations. Overall, improvements in macroscopic lesions were observed in all sample dogs, characterized by reduced pruritus, erythema, macules, papules, pustules, crusts, scabs, scaling, hyperpigmentation, and lichenification, as well as hair regrowth in areas affected by alopecia. In conclusion, coconut oil application is effective in improving the healing of macroscopic lesions in dogs with atopic dermatitis.